Moving the dial on identifying endotypes of asthma from early life. Issue 3 (29th September 2022) - Perrem, Lucy; Subbarao, Padmaja
No longer recognised as a single disease entity with a "one size fits all" approach to treatment, asthma is an umbrella diagnosis spanning different endotypes and clinical phenotypes. The discovery of T2 inflammation as a driver in many asthma patients transformed our understanding of this disease and inspired the discovery of targeted biological therapies [1]. T2 inflammation is mediated by cytokines including interleukin (IL)-4, IL-5 and IL-13, which then regulate the production of measurable biomarkers including IgE, blood and sputum eosinophils, and fractional exhaled nitric oxide ( F eNO ) [2 ]. There is a need for stable biomarkers of endotype for asthma across the lifecourse to provide earlier precision medicine approaches https://bit.ly/3PAS19i